Question
h) \( 6 \cdot 7-6^{0} \cdot 7^{0}= \)
Ask by Knight Mckenzie. in Chile
Nov 05,2024
Real Tutor Solution
Tutor-Verified Answer
Answer
El resultado es 41.
Solution
Para resolver la expresión \( 6 \cdot 7 - 6^{0} \cdot 7^{0} \), primero calculamos cada parte:
1. \( 6 \cdot 7 = 42 \)
2. \( 6^{0} = 1 \) (cualquier número elevado a la potencia de 0 es 1)
3. \( 7^{0} = 1 \)
Ahora, multiplicamos los resultados de \( 6^{0} \) y \( 7^{0} \):
\( 6^{0} \cdot 7^{0} = 1 \cdot 1 = 1 \)
Finalmente, sustituimos estos valores en la expresión original:
\( 42 - 1 = 41 \)
Por lo tanto, el resultado es:
\( 41 \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Extra Insights
Let's break it down! First, \( 6^0 \) and \( 7^0 \) are both equal to 1, because any non-zero number raised to the power of 0 is 1. So, we have: \[ 6 \cdot 7 - 1 \cdot 1 = 6 \cdot 7 - 1. \] Calculating \( 6 \cdot 7 \) gives us 42. Now, if we subtract 1 from 42, we get: \[ 42 - 1 = 41. \] So, the final answer is \( 41 \). In summary, \( 6 \cdot 7 - 6^0 \cdot 7^0 = 41. \)